Functional and anatomical dissection of feeding circuits - Atasoy, Deniz; Sternson, Scott M. (Wiley, 2016)
This chapter reviews the application of new genetically encoded tools in feeding circuits that regulate appetite. Rapid activation and inhibition of agouti related peptide (AgRP) neurons conclusively established a causal role for rapid control of food intake. Chemogenetic activation of AgRP neurons using hM3Dq avoids the invasive protocols required for ChR2 activation. ChR2 distributes into axons, and selective optogenetic activation of AgRP neuron axon projection fields in distinct brain areas was used to examine their individual contribution to feeding behavior. Some of the brain areas targeted by AgRP neuron axon projections have been examined further for cell type specific control of appetite. Rodents with bed nucleus of stria terminalis (BNST) lesions show hyperphagia and obesity, indicating that reduced BNST output promotes feeding. pro-opiomelanocortin (POMC) neurons regulate feeding over longer timescales. parabrachial nucleus (PBN) neurons have a powerful inhibitory role on food intake, but their inhibition does not strongly elevate food intake.
Keywords: Agouti Related Peptide Neurons; Appetite Regulation; Bed Nucleus of Stria Terminalis; Chemogenetic Tools; Feeding Circuits; Obesity; Optogenetic Tools; Parabrachial Nucleus Neurons; Pro-Opiomelanocortin Neurons